Development of an optimized protocol for protoplast-to-plant regeneration of selected varieties of Brassica oleracea L. - Katarzyna Stelmach-Wityk; Kamil Szymonik; Ewa Grzebelus; Agnieszka Kiełkowska (BMC Plant Biology)
Abstract Background Brassica oleracea L. is a key plant in the Brassicaceae family, known for popular vegetables like cabbage, broccoli, kale and collard. Collard (B. oleracea var. viridis) is a non-heading leafy vegetable grown in urban farms and community gardens in the United States and Europe. Improving collard and other Brassica germplasm can benefit from both traditional and new plant breeding technologies (NPBTs), such as CRISPR-Cas mediated transformation. An efficient transformation or protoplast fusion can only be achieved with a robust and reproducible protocol for protoplast-to-plant regeneration. This research focuses on optimizing in vitro culture conditions to enhance cell divisions, microcallus formation, and the regeneration of shoots and roots in four Brassica oleracea varieties, including collard. Results The protocol of protoplast release, purification and immobilization was optimized to obtain a suitable number and quality of protoplasts from seven cultivars of B. oleracea. The protoplast isolation efficiency after digestion of young leaves in optimized enzyme solution reached on average 2.5 × 106 of cells per gram of fresh weight. Protoplasts were embedded in thin alginate layers and subjected to culture in three different media. Protoplasts of all studied cultivars were viable (88.2%), underwent cell wall resynthesis and re-entered mitotic divisions in the 5th day of culture. After 30 days of culture, protoplast-derived cells of all the tested cultivars formed microcallus. Six cultivars regenerated shoots, although the shoot formation efficiency strongly depended on the genotype and composition of the regeneration medium. The regeneration medium supplemented with 1 mg l−1 of NAA, 1 mg l−1 of 2iP, 0.02 mg l−1 GA3 and with 2% of mannitol showed the highest shoot formation efficiency for five cultivars of B. oleracea. Conclusions The results of this research have led to the development of a robust protoplast-to-plant regeneration protocol for four varieties of B. oleracea that could be exploited as a tool for production of transformants and somatic hybrids. Furthermore, we present the first successful regeneration of protoplast-derived plants of collard, an overlooked but valuable variety of Brassica oleracea.